Can cell-free DNA testing be used in pregnancies with isolated fetal omphalocele? Preliminary evidence from cytogenetic results of prenatal cases. (16th February 2021) - Xu, Li-Li; Zhen, Li; Lou, Ji-Wu; Tang, Hai-Shen; Pan, Min; Han, Jin; Yang, Xin; Li, Dong-Zhi
Abstract: Objective: To evaluate whether cell-free DNA (cfDNA) testing could replace an invasive procedure in pregnancies with isolated fetal omphalocele. Study design: This was a retrospective study of all pregnancies with sonographically detected fetal omphalocele at three tertiary referral centers between 2012 and 2016. Invasive diagnostic testing was performed for genetic investigations using conventional karyotyping or chromosomal microarray. cfDNA testing was assumed to be offered to patients with isolated fetal omphalocele for screening for common aneuploidies. Results: Invasive genetic testing was performed in a total of 107 pregnancies with a fetal omphalocele. Abnormal karyotype was found in 66% (31/47) of nonisolated omphalocele cases and in 1.7% (1/60) of isolated omphalocele cases. No pathogenic copy number variations (CNVs) were detected in 59 cases with isolated omphalocele and normal karyotype. If cfDNA screening was used in cases with isolated omphalocele, the affected fetus with trisomy 18 would be detected, and no rare chromosomal aberrations or submicroscopic pathogenic CNVs would be missed. Conclusions: cfDNA testing could be recommended for prenatal genetic evaluation in pregnancies with isolated fetal omphalocele after thorough pretest counseling. Key Message: A very low percentage of aneuploidies and rare chromosomal/subchromosomal abnormalities are found in prenatal cases of isolated omphalocele. It seems that for pregnancies with isolated omphalocele, cfDNA testing represents an alternative for patients who choose to continue the pregnancies and are reluctant to undertake invasive diagnostic testing.